Nigeria: Impacts of COVID-19 on Production, Poverty & Food Systems - Andam, Kwaw S.; Edeh, Hyacinth; Oboh, Victor; Pauw, Karl; Thurlow, James (2020)
Kwaw Andam, Hyacinth Edeh, Victor Oboh, Karl Pauw & James Thurlow One in a series of initial assessments of the economy-wide impacts of COVID-19 lockdowns in several African countries